Identifying key competencies for supporting second victims in different contexts: a scoping review - José Joaquín Mira; Kris Vanhaecht; Deborah Seys; Massimiliano Panella; Reinhard Strametz; Paulo Sousa; Andrea Conti; Alicia Sánchez-García; Clara Pérez-Esteve; Eva Potura (BMJ Open)
Background Providing support to second victims in workplaces is crucial for maintaining high-quality performance. Peer support approach has proven to be one of the most effective and well-accepted approaches. However, the specific competencies required for peer supporters remain unclear. This review aims to address this gap by identifying and categorising these competencies.Objective This scoping review examines the competencies (skills, attitudes and knowledge) needed to support workers where the pressure of their roles may lead to errors that could cause harm to others. In such situations, these individuals may experience intense feelings of responsibility, potentially impacting their ability to perform their duties. In the healthcare sector, these workers are commonly referred to as ‘second victims’.Eligibility criteria This review includes studies that define the competencies necessary for peer supporters assisting second victims in any industry. It covers all professional roles susceptible to human errors affecting people’s well-being. The focus is on peer support and psychological first aid, encompassing relevant competencies, attitudes and knowledge for addressing safety-related incidents and workplace errors.Sources of evidence The scoping review was conducted following Arksey and O’Malley’s framework and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines. Studies were identified through a comprehensive search of databases, including Embase, ProQuest, PsycINFO, PubMed, Scopus and Web of Science. References from eligible studies were also considered.Charting methods Data were extracted and categorised into competency domains through a standardised process. Two reviewers independently performed data extraction, with discrepancies resolved by consensus.Results A total of 34 studies were included in the review. Across five identified domains, 91 specific and 30 general competencies were categorised. Additionally, the review identified 29 types of peer-based interventions designed to support professionals following incidents or stressful situations.Conclusions The findings underscore the need for well-defined competencies for peer supporters of second victims, emphasising training in communication, emotional support and role-specific knowledge. Tailoring peer support programmes to the professional context and industry-specific characteristics is essential for providing effective assistance.